Cost-effectiveness of a complex workplace dietary intervention: an economic evaluation of the Food Choice at Work study. Issue 3 (3rd March 2018) - Fitzgerald, Sarah; Murphy, Aileen; Kirby, Ann; Geaney, Fiona; Perry, Ivan J
Abstract : Objective: To evaluate the costs, benefits and cost-effectiveness of complex workplace dietary interventions, involving nutrition education and system-level dietary modification, from the perspective of healthcare providers and employers. Design: Single-study economic evaluation of a cluster-controlled trial (Food Choice at Work (FCW) study) with 1-year follow-up. Setting: Four multinational manufacturing workplaces in Cork, Ireland. Participants: 517 randomly selected employees (18–65 years) from four workplaces. Interventions: Cost data were obtained from the FCW study. Nutrition education included individual nutrition consultations, nutrition information (traffic light menu labelling, posters, leaflets and emails) and presentations. System-level dietary modification included menu modification (restriction of fat, sugar and salt), increase in fibre, fruit discounts, strategic positioning of healthier alternatives and portion size control. The combined intervention included nutrition education and system-level dietary modification. No intervention was implemented in the control. Outcomes: The primary outcome was an improvement in health-related quality of life, measured using the EuroQoL 5 Dimensions 5 Levels questionnaire. The secondary outcome measure was reduction in absenteeism, which is measured in monetary amounts. Probabilistic sensitivity analysis (Monte Carlo simulation) assessed parameter uncertainty. Results: The system-level intervention dominated the education and combined interventions. When compared with the control, the incremental cost-effectiveness ratio (€101.37/quality-adjusted life-year) is less than the nationally accepted ceiling ratio, so the system-level intervention can be considered cost-effective. The cost-effectiveness acceptability curve indicates there is some decision uncertainty surrounding this, arising from uncertainty surrounding the differences in effectiveness. These results are reiterated when the secondary outcome measure is considered in a cost–benefit analysis, whereby the system-level intervention yields the highest net benefit (€56.56 per employee). Conclusions: System-level dietary modification alone offers the most value per improving employee health-related quality of life and generating net benefit for employers by reducing absenteeism. While system-level dietary modification strategies are potentially sustainable obesity prevention interventions, future research should include long-term outcomes to determine if improvements in outcomes persist. Trial registration number: ISRCTN35108237 ; Post-results.